Monster or great fish? Peter Benchley's Jaws as ecocritical text. (1st September 2016) - Robinson, David
ABSTRACT: This article considers the bestselling novel, Jaws, as a text that reflects a range of attitudes towards the environment and provides points of debate regarding the manner in which human beings conceptualise their environment and the relationship humans have with the environment. In addressing this popular text the article explores several elements of ecocritical theory through reference to the work of Greg Garrard, Cheryll Glotfelty, Timothy Clark, and Terry Gifford. The article also makes reference to J. J. Cohen's monster theory as an analytical tool in addressing the novel. In addition, the author locates the novel in an historical perspective by examining the relationship that exists between humans and the ocean, particularly sharks, through reference to the work of Michael Capuzzo and Juliet Eilperin.